Exploiting the potential of vector control for disease prevention - H Townson; MB Nathan; M Zaim; P Guillet; L Manga; R Bos; M Kindhauser (Bulletin of the World Health Organization, 2005)
Although vector control has proven highly effective in preventing disease transmission, it is not being used to its full potential, thereby depriving disadvantaged populations of the benefits of well tried and tested methods. Following the discovery of synthetic residual insecticides in the 1940s, large-scale programmes succeeded in bringing many of the important vector-borne diseases under control. By the late 1960s, most vector-borne diseases - with the exception of malaria in Africa - were no longer considered to be of primary public health importance. The result was that control programmes lapsed, resources dwindled, and specialists in vector control disappeared from public health units. Within two decades, many important vector-borne diseases had re-emerged or spread to new areas. The time has come to restore vector control to its key role in the prevention of disease transmission, albeit with an increased emphasis on multiple measures, whether pesticide-based or involving environmental modification, and with a strengthened managerial and operational capacity. Integrated vector management provides a sound conceptual framework for deployment of cost-effective and sustainable methods of vector control. This approach allows for full consideration of the complex determinants of disease transmission, including local disease ecology, the role of human activity in increasing risks of disease transmission, and the socioeconomic conditions of affected communities.